"The effect of style is seen before you hear it in the collection of grammar. The Arabic language for students of the second intermediate grade (Journal of the College of Basic Education, 2023)
Research abstract:The current research aims to find out (the effect of the “look before you hear” method on the collection of Arabic grammar for second-grade intermediate students), and to verify the current research, the researcher formulated the following zero hypothesis: “There are no statistically significant differences at the level of significance (0.05) between the average The scores of the students of the experimental group who studied according to the method (see before you hear) in the achievement of the Arabic grammar subject, and the mean scores of the students of the control group who studied according to the traditional method the same material in achievement, and between the students of the experimental group who studied according to the method of (see before you hear) in The achievement of the Arabic grammar subject and the average grades of the female students of the control group who studied the traditional method in the same subject in achievement. For the second intermediate grade in (Al-Hawraa School for Girls), and the study began on Sunday 10/13/2021. The researcher prepared an achievement test consisting of (30) items of the multiple choice type. The researcher verified the validity of the numbers. A test by presenting it to a group of arbitrators and experts in the field of teaching methods, measurement and evaluation, and the researcher verified the stability and difficulty of the test and distinguishing its paragraphs. Upon completion of the experiment. The achievement test was applied to the experimental and control groups on Wednesday 4/3 2022, and the researcher used statistical methods (chi-square test, t-test for two independent samples, coefficient of ease, difficulty and discrimination, Pearson's correlation coefficient for the essay items, Bonnetbacerial correlation coefficient for thematic items, Cooper's equation, coefficient Alfacron-Bach equation for the effect value, Cohen to determine the magnitude (d).The results revealed that there were statistically significant differences between the average scores of the students of the two experimental groups and the control group who studied according to the method of (building and maintaining confidence) and between the average scores of the students of the control group who studied according to the traditional method, in favor of the experimental group, and in the light of the results of the study, the researcher reached To a number of conclusions related to teaching using the method of (building and maintaining confidence) and related recommendations and proposals.Keywords: (effect, look, achievement)